Series method to solve conformable fractional ric-cati differential equations - Al Masalmeh, Mohammed (International Journal of Applied Mathematical Research, 2017)
This paper investigates and states some properties of conformable fractional derivative, Further Study and applies the series solution for a case of conformable fractional Riccati deferential equation with variable coefficients â€œwhich is arising in stochastic gamesâ€ or â€œhyperbolic boundary control." Recently, Prof. Roshdi Khalil introduced a new and interesting definition for the C F D, which is simpler than the previous definition in Caputo and Riemann-Liouville. It leads to many extensions of the classical theorems in calculus.